The Effect of Corporate Governance Mechanisms on Firm Perfomance: Malaysian Perspective - Kamarul Zaman, Sali (2011)
Numerous studies have looked at the implications of corporate governance structures on company performance. Although the literature is not unanimous in its conclusions,the weight of opinion is that there is a significant relationship between governance mechanisms and structures and firm performance. The aim of this research is to study the effect,if any of corporate governance mechanisms, particularly corporate ownership structure, corporate board,and compensation packages,on the performance of Malaysian public listed companies.The literature on these multidimensional governance parameters on firm performance in the context of Malaysia is lacking. Using sample of large publicly traded Malaysian companies, in particular in the properties and plantations sectors, this research examine the effect of institutional investor monitoring,board size and independence,and executive compensation on firm performance as measured by Tobin’s Q, return on assets (ROA) and return on equity (ROE).Results show that there is significant but weak relationship between corporate governance mechanisms in particular corporate board structure and executive compensation, with company performance.These findings suggest that there are other factors which have larger influence on the profitability and performance of companies. Nevertheless, the level of compliance with the Malaysian Code of Corporate Governance is high among the public listed companies.